Alterations in gene expression associated with invasion of RAS-mutant thyroid tumors and their potential diagnostic and therapeutic utility - Vincenzo Condello; William R Doerfler; Alyaksandr V Nikitski; Daniel M Spagnolo; Ian J Fornal; Gavin M Schmidt; Abigail I Wald; Marina N Nikiforova; Yuri E Nikiforov (European Thyroid Journal)
Introduction: Mutations of RAS genes are detected in a spectrum of follicular-patterned thyroid tumors. Preoperative prediction of invasive cancers based on the presence of RAS mutation alone is challenging because non-invasive and invasive tumors tend to have similar sonographic and cytologic features. The aim of this study was to perform clinicopathologic and molecular analyses of RAS-mutant tumors, identify molecular and clinical markers associated with invasiveness, and determine their diagnostic and therapeutic potentials. Methods: We collected clinicopathologic characteristics and performed RNA-seq on 48 surgically resected RAS-mutant thyroid tumors (23 non-invasive and 25 invasive). A classifier using expression data of selected invasiveness markers and clinical parameters was applied to an independent set of 54 RAS-mutant fine-needle aspiration (FNA) samples to predict invasion. Selected markers were investigated in vitro and in vivo. Results: On RNA-seq analysis, invasive RAS-mutant tumors showed different gene expression profiles compared to non-invasive tumors. Expression levels of six selected genes (CA12, CD44, LRP4, ECM1, FN1, and CRABP1) were associated with invasiveness on qRT-PCR. Expression levels of these genes plus nodule size predicted invasion in RAS-mutant FNA samples with 95% sensitivity and 89% specificity. siRNA silencing and chemical inhibition of CA12 reduced invasion of RAS-mutant human thyroid cells. Treatment of RAS-mutant xenografts with CA12 inhibitors arrested tumor growth. Conclusions: Development of invasion in RAS-mutant tumors is associated with significant alteration in gene expression. Expression levels of six genes and nodule size may predict invasion in RAS-mutant thyroid nodules, whereas chemical inhibition of CA12 may have a potential therapeutic effect in RAS-mutant tumors.